A 'think aloud' exercise to develop self-awareness of clinical reasoning in students. (2nd August 2020) - Downs, Simon; Halls, Amy
Abstract : Aims: This study aimed to evaluate the 'think aloud' teaching exercise's ability to develop clinical reasoning skills of student paramedics, and to ascertain its feasibility as an ongoing method to enhance clinical reasoning teaching and potentially alleviate problems around applying theoretical learning to practice. Methods: A qualitative approach was taken to seek the opinions and experiences of students taking part in the activity to determine levels of enjoyment, how relatable it was to students, and awareness of the skills it was intended to develop. Data collected via an online survey tool were analysed to identify themes and comments. Findings: Student enjoyment and engagement were evident, and the exercise permitted independence of thought and working, promoting self-appraisal among students of the effectiveness of the working strategy. Conclusion: The results of this case study indicate that the think aloud exercise could be effective in developing students' clinical reasoning skills. It complements established teaching strategies, such as core lectures, seminars and supervised practice.